Édito - Pour une histoire transnationale de l'éducation - Sébastien-Akira Alix; Pierre Kahn (Nantes Université, 2023)
Transnational history has grown significantly over the last three decades. This approach offers new research perspectives for historical inquiries by focusing on processes of interconnection that often transcend national boundaries. In line with this historiographical trend, this special issue aims to analyze, from a historical perspective, the national and international circulation of actors, knowledge and models in education drawing on case studies from the 19th- and 20th-centuries. This special issue additionally offers a survey of the historiography of transnational circulations in education in the late modern and contemporary periods.